Unusual Cases of Multiple Symmetrical Lipomatosis with Neurological Disorders - Triantafyllou, N. I.; Zalonis, I.; Kararizos, G.; Gkiatas, K.; Christidi, F.; Kararizou, E. (Clinical medicine & research, 2009)
Multiple symmetrical lipomatosis (MSL) is a rare disorder of unknown etiology defined as the presence of multiple and symmetrical fatty accumulations, usually involving the upper trunk, neck and head. Frequently associated findings include diabetes mellitus, hyperlipidemia, liver disease, hypothyroidism and polyneuropathy of unknown origin, but nevertheless, there are published reports of cognitive disorders in patients with MSL. We describe two unusual cases (38-year-old and 45-year-old Greek men) of MSL who presented with polyneuropathy and memory disorders. This is the first description of memory disorders in patients with MSL. We propose that Mini-Mental State Examination and assessment of cognitive functions should be performed for all patients with MSL. The underlying mechanism in our patients remains unknown, and this question should be the subject of a future study.